2013
DOI: 10.1164/rccm.201209-1732oc
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Previous Use of Inhaled Corticoids on the Development of Pleural Effusion in Community-acquired Pneumonia

Abstract: Prior treatment with ICS in a population of patients with different respiratory chronic disorders who develop pneumonia is associated with lower incidence of parapneumonic effusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
46
1
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(51 citation statements)
references
References 39 publications
3
46
1
1
Order By: Relevance
“…Although the use of inhaled corticosteroids in COPD patients has been demonstrated to be useful in the reduction of exacerbation events 16,17 and in protection against the development of complicated forms of hospitalized community-acquired pneumonia. 14,15 On the other hand, the long-term use of inhaled corticosteroids increases the risk of pneumonia, [18][19][20] especially with fluticasone. 20 Our study, performed in subjects with COPD exacerbation but without pneumonia, demonstrates that inhaled corticosteroids have no detrimental effect on the development of complications on admission or in other outcomes collected during the clinical course.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the use of inhaled corticosteroids in COPD patients has been demonstrated to be useful in the reduction of exacerbation events 16,17 and in protection against the development of complicated forms of hospitalized community-acquired pneumonia. 14,15 On the other hand, the long-term use of inhaled corticosteroids increases the risk of pneumonia, [18][19][20] especially with fluticasone. 20 Our study, performed in subjects with COPD exacerbation but without pneumonia, demonstrates that inhaled corticosteroids have no detrimental effect on the development of complications on admission or in other outcomes collected during the clinical course.…”
Section: Discussionmentioning
confidence: 99%
“…13 In hospitalized COPD patients with community-acquired pneumonia, inhaled corticosteroids protect against more severe forms 14 and against complicated pleural effusion. 15 These beneficial effects in community-acquired pneumonia may be explained by down-regulation of the inflammatory response.…”
Section: Introductionmentioning
confidence: 99%
“…Some of these studies also reported an improvement in other pertinent outcomes among patients using ICS, such as decreased risk of parapneumonic effusion and less frequent need for mechanical ventilation and vasopressors (10,11,14). Pneumonia ascertainment was better and more systematic in these observational studies than in the RCTs analyzed in a previous systematic review (15).…”
mentioning
confidence: 84%
“…The short-term mortality after hospitalization for pneumonia was again decreased (relative risk, 0.75 [95% CI, 0.69-0.82]). Four other studies, encompassing only one-fourth of patients, demonstrated no increased risk of pneumonia-related death with the wide CIs (8,13,14,30). Retrospective, observational design adds to the above-mentioned imprecision of assessment of pneumoniarelated mortality.…”
Section: Pneumonia-related Mortalitymentioning
confidence: 95%
“…Меншу частоту ускладнення НП ексудативним плевритом у хворих з астмою (3,4% проти 5,2%, p<0,001) та хронічним об-структивним захворюванням легень (3,4% проти 5,2%, p<0,001) описували F. [10]. Існують відомості про протективний вплив регулярного прийому інгаляційних кортикосте-роїдів на розвиток цього ускладення НП [3].…”
unclassified